Validitas dan Reliabilitas Instrumen Penilaian Afektif Mata Kuliah Komunikasi dalam Praktik Kebidanan: Validity and Reliability of the Affective Assessment Instrument for the Communication Course in Midwifery Practice - Teresia Suminta Rotua Situmorang; Annisa Eka Permatasari; Reza Bintangdari Johan; Nur Aisyah Laily; Idha Farahdiba; Nurrahmi Umami (Jurnal Midwifery, 2023)
Introduction: The affective domain is important for assessing student attitudes and behavior in the learning process, but the implementation is still lacking. So far, affective assessment is still implied in the assessment of the cognitive domain, so that the assessment of the affective domain is still carried out with cursory observations. Affective domain assessment needs to be supported using tests that match the characteristics of learning objectives. Attitude assessment can be subjective so we need an instrument that is able to measure objectively. This research aims to evaluate the feasibility of an affective ability assessment instrument in the Communications in Midwifery course at the Faculty of Health Sciences, University of Borneo Tarakan. Methods: This type of research is descriptive. The research sample was 30 midwifery students who were taken randomly. Data collection used an affective assessment questionnaire in the communication course in midwifery practice. Results: The results of the validity test research carried out, 22 items were declared valid out of 25 statement items (rcount > 0.361) and the instrument reliability test was 0.858 (alpha > 0.7). Conclusion: affective assessment instruments can be declared feasible and reliable so that they can be used to measure students' affective abilities